SOCIO-HISTORICAL FACTORS OF THE DYNAMICS OF RELIGIOUS IN UKRAINE - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article analyzes the impact of historical features religious development of Ukrainian society on the current state and directions for future dynamics of religious consciousness in Ukraine. The peculiarities of these main stages of development of religious consciousness in Ukraine.